Effects of External Circumstances on the Implementation of the Education Sector Policy on HIV and AIDS in Public Secondary Schools in Kajiado County - Wanjira , Lucy; Kitainge , Kisilu (African Journal of Education,Science and Technology (AJEST), 2014)
The effectiveness of an organization is reflected in its ability to not only formulate policy but also execute such policies. The Ministry of Education Science and Technology (MoEST) developed the Education Sector Policy on HIV and AIDS in 2004 and tasked school managers amongst other stakeholders with implementation. Care and support of learners made vulnerable by HIV and AIDS in academic institutions has been advanced by the government following realization that there is need to ensure that their academic journeys are not interrupted. This study investigated the effects of external circumstances on the implementation of the Education Sector Policy on HIV and AIDS and on provision of care and support to orphaned and vulnerable learners (OVLs). The study was carried out in Kajiado County. The study employed descriptive research design. The study targeted public secondary schools in the County. Simple random sampling was used to sample twenty four schools across the five sub counties of Kajiado County. Purposive sampling was used thereafter to select head teachers, deputy head teachers, class teachers and guidance and counselling teachers in the sampled schools and who were the respondents in this study. To collect data, questionnaires and interviews were used. Descriptive statistics was used to analyze data. The study findings indicated that external circumstances influence implementation of the Education Sector Policy on HIV and AIDS and on provision of care and support to OVLs. The study recommended that there was need to facilitate further training of respondents in counselling and on HIV and AIDS in schools. The study further recommended that school managers rally the support of local authorities in implementation of the policy and that teachers be given incentives to attract them to willingly participate in HIV and AIDS related programs and activities in schools.